STUDY OF HYBRID FIBER REACTIVE POWDER CONCRETE CHARACTERISTICS WITH VARIATIONS OF MICRO POLYPROPYLENE FIBER AND STEEL FIBER CONTENT - Trisakti Paiding Lewa, Shandy
The main principle in improving the performance of RPC is to use cement or pozzolanic material to strengthen the Interfacial Transition Zone (ITZ) between the mortar matrix and the fine aggregate by reducing the w/c ratio, eliminating coarse aggregate in the mixture, and application of heat during curing. However, by eliminating coarse aggregate in the RPC mixture, the interlocking effect does not occur which can dissipate the cracks that occur during failure. This can make RPC behavior very brittle. To replace the function of coarse aggregate in crack dissipation, the use of fiber is added to create a multiple crack bridging effect This study focuses on the effect of adding micro polypropylene fiber to the behavior of RPC mixtures containing 1% Steel Fiber. Variations in addition of micro polypropylene fiber ranged from 0.06% to 0.1% of the volume fraction. The tests carried out were fresh concrete tests (slump flow, J-Ring test, and slump loss) and hard concrete tests (Compressive Strength, Flexural Strength, Direct Tensile Strength, and Fracture Energy). The addition of steel fiber with a concentration of 1% can cause a decrease in workability. Mixtures containing 1% Steel Fiber and added Micro Polypropylene Fiber with a volume fraction of 0.06% - 0.1% can cause a significant decrease in workability due to a large aspect ratio and can cause additional friction in the mixture. The decrease caused by the addition of fiber ranged from 2.87% - 15.83%. The compressive strength of RPC did not increase significantly when added fiber to the mixed matrix. However, the application of Hot Water Treatment during the treatment process will increase the RPC compressive strength from 90.1 MPa to 114.5 MPa (2% - 19%). The increase due to the addition of micro polypropylene fiber (MPF) to the SF1 mixture increased the flexural strength by 7.16 MPa to 15.62MPa (42% - 59%) for Normal Curing and 6.33 MPa to 15.09 MPa (36% - 38%) for Hot Water Treatment. The increase due to the addition of MPF to the SF1 mixture increased the tensile strength by 1.95 MPa to 4.26 MPa (19% - 43%) for Normal Curing and 2.63 MPa to 4.87 MPa (7% - 44%) for Hot Water Treatment. Fracture energy also increases when MPF is added to SF1 by 0.149 N/mm to 2.33 N/mm (9 – 16 times) for Normal Curing and 0.153 N/mm up to 2.94 N/mm (15 – 19 times) for Hot Water Treatment.